PLGA-based herb Toosendanin delivery system for efficient therapy of oral squamous cell carcinoma - Lingling Chen; Cheng Feng; Zhenyu Shi; Jianzhe Wang; Tao Wang; Yibing Wang; Lisong Lin; Ye Wu (BMC Complementary Medicine and Therapies)
Abstract Oral squamous cell carcinoma (OSCC) is a significant public health issue worldwide. Conventional chemotherapeutic agents do not adequately meet the treatment demands because of their low efficacy and adverse side effects. Toosendanin (TSN) is a natural extract with potential anticarcinogenic activity. Nonetheless, its clinical application is constrained by its poor water-solubility and limited bioavailability. Therefore, we prepared TSN-loaded poly (lactic-co-glycolic acid) nanoparticles (TSN-PLGA NPs) to improve the water-solubility of TSN and potentially further enhance its bioavailability. TSN-PLGA NPs were synthesized and characterized, and we showed their exceptional properties for sustained release in vitro. TSN-PLGA NPs exhibited cytotoxic effects against OSCC cells, potentially inhibiting proliferation and promoting apoptosis by inducing cell-cycle arrest in the S-phase at low concentrations. RNA-sequencing analysis revealed the potential regulation of OSCC cell viability by TSN-PLGA NPs through signaling pathways such as JAK/STAT and PI3K–Akt. Furthermore, animal models provided evidence of the in vivo antitumor activity of TSN-PLGA NPs, with no observable side effects in nude mice, which indicated potential biocompatibility. Consequently, TSN-PLGA NPs may be a promising chemotherapy candidate for OSCC treatment.